Efektivitas Bimbingan Kelompok untuk Meningkatkan Perilaku Asertif Anak Asuh di Panti Asuhan Aisyiyah Putri Pasar Bawah - Nur Aini; Syawaluddin Syawaluddin (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research examines the assertive behavior of some of the foster children at the Aisyiyah Putri Pasar Bawah Orphanage who tend to show a less assertive attitude as seen in the way they communicate with other people, difficulty in choosing the right language to refuse invitations, difficulty in controlling emotions, difficulty in express your feelings and thoughts. The aim of this research was to improve the assertive behavior of orphanage children and their ability to communicate well. This research uses a quantitative experimental method with a one group pretest-posttest experimental research design. The population in this study was all children from orphanages. The sample in this study used a purposive sampling technique, namely admitted children who had a less assertive attitude. The research subjects were children from orphanages who had less assertive behavior which was obtained from the results of observations and interviews. The data analysis technique uses the Wilcoxon rank test. The research instrument uses an assertive behavior questionnaire. The results of this research were seen from the pretest and posttest with an increase in each child after carrying out group guidance. The results of the research show a value of 0.012 < 0.05, so it can be concluded that group guidance has proven effective in increasing the assertive behavior of children at the lower market Aisyiyah girls' orphanage.